The representation type of elementary abelian p-groups with respect to the modules of constant Jordan type - Bondarenko, V.M.; Lytvynchuk, I.V. (Algebra and Discrete Mathematics, 2012)
We describe the representation type of elementary abelian p-groups with respect to the modules of constant Jordan type and offer two conjectures (for such modules) in the general case, one of which suggests that any non-wild group is of finite representation type in each dimension.